Food-Grade Encapsulation Systems for (−)-Epigallocatechin Gallate - Shi, Meng (Molecules, 2018)
(−)-Epigallocatechin gallate (EGCG) has attracted significant research interest due to its health-promoting effects such as antioxidation, anti-inflammation and anti-cancer activities. However, its instability and poor bioavailability have largely limited its efficacy and application. Food-grade materials such as proteins, carbohydrates and lipids show biodegradability, biocompatibility and biofunctionality properties. Food-grade encapsulation systems are usually used to improve the bioavailability of EGCG. In the present paper, we provide an overview of materials and techniques used in encapsulating EGCG, in which the adsorption mechanisms of food-grade systems during in vitro digestion are reviewed. Moreover, the potential challenges and future work using food-grade encapsulates for delivering EGCG are also discussed.